Transfection efficiency of chitosan microspheres: effect of DNA topology - (:unkn) unknown (EDITIONS SANTE, 2003)
This study investigates the effect of the topology of the encapsulated plasmid DNA on its in vitro transfection efficiency, using two different plasmids [large pMK3 (7.2 kb) and small pUC18 (2.69 kb)]. DNA-chitosan microspheres containing a mixture of a supercoiled (sc) and an open circular (oc) form, ora linear form, were prepared using a complex coacervation process. Microsphere properties such as size and in vitro release pattern were evaluated. Topology of the plasmid DNA was assessed by using agarose gel electrophoresis. The mean size of the microspheres was about 3.4-3.7 mum. The in vitro release of plasmid DNA from chitosan microspheres indicated a sustained release characteristic. For the in vitro transfection study, the mouse fibroblast cell line (L-strain) was used. Transfection of encapsulated sc + oc forms mixture and linearised form were compared, the results showed that an encapsulated sc + oc mixture has higher level beta-galactosidase expression. For the in vivo transfection study, free and encapsulated forms were injected into the anterior tibialis muscle of the rats. At time intervals, biopsies were performed and beta-galactosidase activity was measured spectrophotometrically using ONPG (o-nitrophenyl-beta-D-galactopyranoside) as a substrate. Chitosan microspheres prepared with the mixture of supercoiled and open circular forms showed a higher beta-galactosidase expression and the proportion of supercoiled to open circular forms in the mixture had no effect on the transfection efficiency of chitosan microspheres. The importance of plasmid DNA size was not clear in these experiments because similar transfection data were obtained with two different sizes of plasmids.
Keywords: gene therapy; DNA topology; transfection; chitosan; controlled release; GENE DELIVERY SYSTEM; PLASMID DNA; IN-VITRO; VIVO